Echinacoside: A promising active natural products and pharmacological agents - Wang Wang; Shujun Jiang; Yang Zhao; Guoxue Zhu (Elsevier, 2023)
Echinacoside, a natural phenylethanoid glycoside, was discovered and isolated from the garden plant Echinacea angustifolia DC., belonging to the Compositae family, approximately sixty years ago. Extensive investigations have revealed that it possesses a wide array of pharmacologically beneficial activities for human health, particularly notable for its neuroprotective and anticancer activity. Several crucial concerns surfaced, encompassing the recognition of active metabolites that exhibited inadequate bioavailability in their prototype form, the establishment of precise molecular signal pathways or targets associated with the aforementioned effects of echinacoside, and the scarcity of dependable clinical trials. Hence, the question remains unanswered as to whether scientific research can effectively utilize this natural compound. To support future studies on this natural product, it is imperative to provide a systematic overview and insights into potential future prospects. The current review provides a comprehensive analysis of the existing knowledge on echinacoside, encompassing its wide distribution, structural diversity and metabolism, diverse therapeutic applications, and improvement of echinacoside bioavailability for its potential utilization.